Process brickwork at the construction site (wall construction) / Yusrizal Aizat Mohd Yusoff - Mohd Yusoff, Yusrizal Aizat (Universiti Teknologi MARA, Perak, 2019)
A wall is a structure that defines an area, carries a load provides security, shelter, or soundproofing or is decorative. The purposes of the walls in buildings are to support roofs, floors and ceilings to enclose a space as part of the building envelope along with a roof to give buildings form; and to provide shelter and security. In addition, the wall may house various types of utilities such as electrical wiring or plumbing. Wall construction falls into two basic categories: framed walls or mass-walls. This report was conducted for the shop lot building at Jelawat, Bachok Kelantan. The objective of this report is to study the method of brickwall construction.